Réponses

2013-04-24T22:35:14+02:00

(x+3)(x-1)= x²-x+3x-3=x²+2x-3     

   

2(x+3)-x-1=2x+6-x-1=x+5                  

 

(x+3)*2+(x-1)=2x+6+x-1=3x+5     

 

2(x-3)(x+3)=(2x-6)(x+3)=2x²+6x-6x-18=2x²-18

 

3(x+3)(x-1)-x-(3-x-1)=(3x+9)(x-1)-x-3+x+1=3x²-3x+9x-9-x-3+x-1=3x²+9x-13

 

-(x+3)²= -(x²+6x+9)= -x²-6x-9

 

(x+3y)(x-4)=x²-4x+3xy-12y

 

x²+3x(x+6)= x²+3x²+18x=4x²+18x

  • Utilisateur Brainly
2013-04-24T22:38:28+02:00

(x+3)(x-1)

x²-x+3x-3

x²+2x-3     

   

2(x+3)-x-1

2x+6-x-1

x+5                  

 

(x+3)*2+(x-1)

2x+6+x-1

3x+5     

 

2(x-3)(x+3)

(2x-6)(x+3)

2x²+6x-6x-18

2x²-18

 

3(x+3)(x-1)-x-(3-x-1)

(3x+9)(x-1)-x-3+x+1

3x²-3x+9x-9-x-3+x-1

3x²+9x-13

 

-(x+3)²

-(x²+6x+9)

-x²-6x-9

 

(x+3y)(x-4)

x²-4x+3xy-12y

 

x²+3x(x+6)

x²+3x²+18x

4x²+18x

 

voilà..... :)